THE USE OF SHOW AND TELL METHOD IN TEACHING VOCABULARY AT THE SECOND YEAR STUDENTS OF JUNIOR HIGH SCHOOL - Ullah, Amrullah; Vivit Rosmayanti; Muhamad Yahrif (Kumpulan Artikel Pendidikan Anak Bangsa (Kapasa) : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This study aimed to know the use of the show-and-tell method in teaching vocabulary the second-year students Of Junior High School SMPS Darul Ulum Panaikang Bantaeng. It consisted of 38 students, 19 students in class controlled and 19 in the experimental class. This research was Quasi-Experimental Design; with experimental and controlled classes. One group was treated as the experimental class and another group was treated as the controlled class. The researchers used pre-test and post-test designs in both experimental and controlled classes. Analysis of the mean score gap in the post-test between the experimental and controlled ensures that the technique used was effective. The mean score of the Experimental class was 9.02 and 5.63 for the Controlled class. It meant the gap between the students’ scores in the Experimental and Controlled class was 3.39. The explanation of the gap between the two classes indicated that the Experimental class showed high improvement than the Controlled class. Based on the result of this study, showing the students' scores were much higher after the treatment in the Experimental class using the show & tell method. The use of the show & tell method was effective toward the students’ vocabulary mastery.